Understanding AI anxiety and GAI adoption among university students in Thailand - Simon Nnaemeka Ajah; Nichanan Sakolvieng; Kaimook Numgaroonaroonroj (Institute of Advanced Engineering and Science, 2026)
Advancements in generative artificial intelligence (GAI) have heightened expectations for its role in educational transformation. This study investigates how AI-related anxiety, perceived usefulness, self-efficacy, and institutional support influence Thai university students’ intention to adopt GAI. Although prior research has explored AI in education, predictors of students’ behavioral intention toward GAI remain insufficiently examined, particularly in the Thai context. A quantitative approach was employed, and data were collected through an online survey from sample of 450 university students in Bangkok, Thailand. Structural equation model (SEM) was used for analysis. Results show that sociotechnical blindness and job‑replacement concerns significantly and positively affect students’ intention to use GAI. Social factors and facilitating conditions increase perceived usefulness and self-efficacy but do not directly influence intention. Perceived usefulness negatively predicts intention, while self-efficacy shows no significant direct effect. Mediation analyses reveal partial effects through perceived usefulness and self-efficacy. AI‑related anxiety has a stronger influence on Thai university students’ adoption of GAI than social or environmental factors, highlighting the need for targeted support to reduce concerns. These findings call for coordinated action among higher education authorities, university policymakers, and students to establish clear, coherent guidelines for AI use in academia. A forward‑looking policy framework is urgently required to ensure responsible and effective integration of AI in Thai higher education.